Interpreting for international conferences : problems of language and communication - Seleskovitch, Danica; Dailey, Stephanie; McMillan, Eric Norman (Washington, D.C. : Pen and Booth, 1994)
Lit.opg.
"Other works by the author": p. 135.
Includes bibliographical references (p. 128) and index.
Keywords: Translating and interpreting; Congresses and conventions